Answer:
(x , y) = ( -4 , 1)
Explanation:
2x + 7y = -1 --------eqn 1
4x - 3y = -19 ----------eqn 2
Step 1: let's pick eqn 1, to make y the subject of the formula
2x + 7y = -1
7y = -1 - 2x
Divide both sides by 7, to make y the subject of the formula
7y/7 = (-1 - 2x)/7
y = (-1 - 2x) / 7
Step 2: substitute y into the equation 2
4x - 3y = -19
4x - 3(-1 - 2x)/7 = -19
Open the bracket
-3 * -1 = +3
-3 * -2x = +6x
4x +( 3 + 6x)/7 = -19
LCM = 7
(28x + 3 + 6x)/7 = -19
(34x + 3)/7 = -19
Cross multiply
34x + 3 = 7 * -19
34x + 3 = -133
34x = -133 - 3
34x = -136
Divide both sides by 34,to get the value of x
34x/34 = -136/34
x = -4
Step 3: substitute x = -4 into eqn 1
2x + 7y = -1
2(-4) + 7y = -1
-8 + 7y = -1
7y = -1 + 8
7y = 7
Divide both sides by 7, to the value of y
7y/7 = 7/7
y = 1
(x , y) = ( -4 , 1)